2005
DOI: 10.1590/s0004-27302005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Associação de tireopatias em uma população de pacientes com diabetes

Abstract: Thyroid Disorders in Diabetic Patients. Objective: To evaluate thyroid function and morphology in all diabetic outpatients from our institution. Methods: From 1996 to 1998, all diabetic patients were submitted to thyroid ultrasonography (US) and serum measurement of free T 4 , TSH, TPOAB, and TRAb. The control group, encompassing outpatients of the same hospital without diabetes and thyroid diseases, was submitted to the same evaluation. A patient was shown to have thyroid disorder when two or more measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
2
0
3
Order By: Relevance
“…This is similar to the rate found in a previous study, 4 in which a frequency of 52% was observed in the same geographical area. This is similar to the rate found in a previous study, 4 in which a frequency of 52% was observed in the same geographical area.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the rate found in a previous study, 4 in which a frequency of 52% was observed in the same geographical area. This is similar to the rate found in a previous study, 4 in which a frequency of 52% was observed in the same geographical area.…”
Section: Discussionsupporting
confidence: 92%
“…Pimenta et al 9 encontraram uma prevalência de hipotireoidismo de 28,8% em um estudo com 132 diabéticos, sendo que 80,9% deles sofriam de diabetes mellitus tipo 2. Gozzano et al 10 estabeleceram uma prevalência de hipotireoidismo de 19,5% em uma amostra com 118 diabéticos tipo 2.…”
Section: Discussionunclassified
“…Many researchers adopt as diagnostic of this pathology an increased tracer retention in the bladder during the performance of radionuclide cystography. The bladder dysfunction would result from neurological, muscular and urothelial injuries, uriginated on hiperglicemia 32,33 .…”
Section: Discussionmentioning
confidence: 99%